The Implementation of Discussion Methods in Improving Science Learning Outcome on Adaptation of Living Things with Their Environment - Bariyatun Bariyatun (Universitas Tanjungpura, 2021)
This study aimed to determine: (1) the results of learning science on the subject of adaptation of living things to their environment before the implementation of the discussion method in fifth-grade students of elementary school, (2) learning outcomes of science learning materials on the adaptation of living things to their environment after the implementation of the discussion method on fifth-grade students at SDN (Public Elementary School) 22 Sungai Ambawang, (3) The improvement of science learning outcomes on the adaptation of living things to their environment after the implementation of the discussion method for fifth-grade students at SDN 22 Sungai Ambawang. This type of research is action research conducted in fifth grade. The results of the study conducted showed that: (1) The results of learning science on the subject of adaptation of living things to their environment before the implementation of the discussion method in fifth grade at SDN 22 Sungai Ambawang were very low, with an average score of 54.5 with students' completeness only reaching six students (30%) and students who did not complete as many as 14 students (70%), (2) The average learning outcomes in the first cycle reached 71 with 9 (45%) students completed and 11 students (55%) had not achieved complete learning. While in the second cycle, the average learning outcomes reached 85.25 with 16 (80%) students who completed and 4 (20%) students who did not complete, (3) The average increase in science learning outcomes in the subject of adaptation of living things to their environment after the application of the discussion method to the fifth-grade students of SDN 22 Sungai Ambawang by 30.75 with an increase in the number of students who completed as many as ten students (50%).